CT appearance of presumptively normal intrathoracic lymph nodes in cats. Issue 10 (October 2020) - Smith, Alexander J; Sutton, Dawn R; Major, Alison C
Objectives: Thoracic CT is commonly performed in cats and has been shown to be more sensitive than radiography for the detection of lymphadenopathy. However, no studies to date have reported the normal CT appearance of feline intrathoracic lymph nodes. The aim of this study was to describe the distribution, number, size and attenuation of presumed normal intrathoracic lymph nodes in cats. Methods: Retrospective analysis of the imaging archive in a teaching hospital identified cats that had undergone thoracic CT and were deemed to have no evidence of either intra- or extrathoracic disease that would influence the size of the intrathoracic lymph nodes. Lymph nodes were classified into lymph centres based on anatomical references. Descriptions of the position of each node, number of nodes in each centre, size of each node and attenuation pre- and post-contrast were recorded. Statistical analysis aimed to assess for correlations between these factors and the age, weight and sex of the subjects. Results: Twenty cats were included in the study. One or more lymph nodes were identified in the sternal (n = 19/20), cranial mediastinal (n = 14/20) and tracheobronchial (n = 15/20) centres, while none were identified in other locations. Size varied between lymph centres and within lymph centres where more than one lymph node was identified. Tracheobronchial and sternal nodes were consistent in location, while mediastinal nodes were variable. All nodes were round to ellipsoid in shape and showed moderate enhancement post-contrast. No significant correlations were found with age, weight or sex. Conclusions and relevance: This study describes the CT characteristics of presumed normal intrathoracic lymph nodes in cats, and only identified nodes in the sternal, cranial mediastinal and tracheobronchial locations. This study serves as a reference point for CT analysis of feline thoracic lymph nodes.